ChemInform Abstract: Enantioselective Syntheses of β‐Amino Alcohols Catalyzed by Recyclable Chiral Fe(III) Metal Complex. Issue 24 (27th May 2016) - Tak, Rajkumar; Kumar, Manish; Kureshy, Rukhsana I.; Choudhary, Manoj Kumar; Khan, Noor‐ul H.; Abdi, Sayed H. R.; Bajaj, Hari C.
Abstract: The title amino alcohols are prepared by asymmetric desymmetrization of meso‐epoxides with various anilines using a series of in situ generated chiral iron complexes based on chiral tridentate ligands as catalyst.